Complete Rectal Prolapse Together with Total Uterine Prolapse Treated Successfuly by Altemeier Operation:A Case Report - Dikensoy, Ebru; Cebesoy, Fatma Bahar; Aybastı, Necdet; Balat, Özcan (Gynecology Obstetrics & Reproductive Medicine, 2009)
Rectal prolapse is a rare gynecological condition and rarely occurs together with uterine prolapse. Birth trauma can be rule out as a cause of rectal prolapse like as uterine prolapse. Perineal proctosigmoidectomy is an effective operation for surgical treatment of rectal prolapse. A fifty five years old women was admitted to our clinic for having masses on her genital area. She had chronic constipation for two years. On the pelvic examination; total prolapse uteri, complete rectal prolapse, and third degree cystocele were seen. Vaginal hysterectomy, colporaphy anterior, colporaphy posterior, and perineal proctosigmoidectomy operations were performed. On the postoperative third day, patient was discharged without any complication. Altemeier (perineal proctosigmoidectomy) is a good choice for surgical treatment of the complete rectal prolapse.